Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I would like to show that

$$ I_{n}=\int_0^1 \frac{x^n \ln x}{x-1}\mathrm dx \sim_{n\rightarrow \infty} \frac{1}{n}$$

Using the change of variable $u=x^n$:

$$ I_{n}=\frac{1}{n^2} \int_0^1 \frac{u^{1/n} \ln u}{u^{1/n}-1} \mathrm du=\frac{1}{n^2}\left(\int_0^1 \ln x \mathrm dx+\int_0^1 \frac{\ln x}{x^{1/n}-1} \mathrm dx \right)=\frac{-1}{n^2}+\frac{1}{n^2}\int_0^1 \frac{\ln x}{x^{1/n}-1} \mathrm dx=o(1/n)+\frac{1}{n^2}\int_0^1 \frac{\ln x}{x^{1/n}-1} \mathrm dx$$

So I have to show that

$$ \int_0^1 \frac{\ln x}{x^{1/n}-1} \mathrm dx \sim_{n \rightarrow \infty} n$$

Could you help me?

share|cite|improve this question
I don't understand the last equality sign in the first line of your computation. – Phira Jun 10 '12 at 11:11
Oddly by my slightly non-rigorous methods, I am getting your original integral ($I_n$) to be roughly $\zeta(2) - H_{n,2}$. So, that would suggest as $n \rightarrow \infty$, the value to go to zero so I am quite baffled by your question at the moment. (Or it could be that I am horribly wrong in my method :-) ) – TenaliRaman Jun 10 '12 at 11:36
up vote 5 down vote accepted

$$\frac{x^n}{x-1} = \frac{x^n-1}{x-1} + \frac{1}{x-1}= \left(1+ x+ \cdots + x^{n-1}\right) +\frac{1}{x-1}.$$

So $$I_n = \int^1_0 (1+x+\cdots + x^{n-1}) \log x + \int^1_0 \frac{\log x}{x-1} dx.$$

Integration by parts shows $ \int^1_0 x^k \log x = -1/(k+1)^2$ and expanding $\log$ by Taylor series will show $\displaystyle \int^1_0 \frac{\log x}{x-1} dx = \frac{\pi^2}{6}$ so $$I_n = \sum_{k=n+1}^{\infty} \frac{1}{k^2}.$$

Thus $$nI_n = \frac{1}{n} \sum_{k=n+1}^{\infty} \frac{1}{(k/n)^2} \to \int_1^{\infty} \frac{1}{x^2} dx=1$$

so $I_n \sim 1/n.$

You can skip showing $\displaystyle \int^1_0 \frac{\log x}{x-1} dx = \frac{\pi^2}{6}$ if you expand $x^n/(x-1)$ as a geometric series from the start.

Instead of using Riemann sums we could also have noted that $1/x^2$ is monotonically decreasing and use the well known theorem that if $f$ is monotone then $\displaystyle \int^n_1 f(x) dx \sim \sum_{k=1}^n f(n).$

share|cite|improve this answer
+1 Typo $I_n \sim 1/n$. Nice, I reached $I_n = \zeta(2) - H_{n,2}$ but somehow thought since $H_{n,2} \rightarrow \zeta(2)$, $I_n$ must go to zero, but your final step was so simply done. – TenaliRaman Jun 10 '12 at 12:01
@TenaliRaman Thanks for pointing that out. All your thoughts are correct, so perhaps you just misunderstood what the question was asking. It is indeed true that $I_n = \zeta(2) - H_{n,2}$ and that $H_{n,2}\to \zeta(2) $ so $I_n \to 0$, but the question was a more precise statement: How quickly does it go to zero? We showed that $\lim_{n\to\infty} nI_n=1$ so for very large values of $n$ we will have $I_n \approx 1/n.$ – Ragib Zaman Jun 10 '12 at 12:09
Ah, it was indeed the case of me completely misunderstanding the question. Thanks for that clarification :-) – TenaliRaman Jun 10 '12 at 12:15
@RagibZaman The $\sum_{k\ge{}n}k^{-2}$ can also be estimated by Euler-Maclaurin formula, which gets $n^{-1}+\frac12n^{-2}+O(n^{-3})$, so $\sum_{k>n}k^{-2} = n^{-1}-\frac12n^{-2}+O(n^{-3})$. – Frank Science Jun 10 '12 at 12:41
@Frank Science In fact we don't even need to full force of Euler-Maclaurin for that estimate, the Trapezoidal rule is enough to tell us that. – Ragib Zaman Jun 10 '12 at 13:16

I propose different approach. First, consider integral: $$J_n = \int_0^1 \frac{x^n -1}{x-1} \, dx$$ than we have $I_n = \tfrac{dJ_n}{dn}$. Observe that: $$J_n = \int_0^1 \frac{x^n - 1 }{x-1} \, dx = H_n \sim \ln n + \ldots$$ So it's now easy to note that: $$I_n \sim \frac{1}{n}$$ for large $n$.

share|cite|improve this answer
Differentiating both sides of an asymptotic formula is troublesome, for example consider $n+\sqrt{n}\sin n \sim n.$ – Ragib Zaman Jun 10 '12 at 11:54
@RagibZaman sure, but here $I_n$ behaves fine enough. – qoqosz Jun 10 '12 at 12:03
@qoqosz This was precisely how I approached to solve and find the value of the integral, though I considered $J_n$ to be $\int_0^1 \frac{x^n - 1}{x - 1}$ since the $J_n$ as currently defined will have a diverging term. $J_n$ then by my definition is simply $H_n$ whose derivative comes out to be $\zeta(2) - H_{n,2}$ as given here. – TenaliRaman Jun 10 '12 at 12:24
@TenaliRaman you're right, I haven't noticed this divergence before. Thanks! – qoqosz Jun 10 '12 at 12:31

Actually, a closed form solution may be given:

$$I_{n}=\int_0^1 \frac{x^n \ln x}{x-1}dx=-\int_0^1[x^n(1+x^2+x^3+...)\ln x]dx=$$

$$=-\sum_{k=0}^\infty \int_0^1 (x^{k+n}\ln x)dx=\sum_{k=0}^\infty\frac{1}{(k+n+1)^2}=$$

$$=\frac{1}{(n+1)^2}+\frac{1}{(n+2)^2}+...=\zeta(2,n+1) $$ where $$\zeta(s,a)=\sum_{k=0}^\infty\frac{1}{(k+a)^s}$$ is so called Hurwitz Zeta Function

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.